Response of Green Gram Demonstrated Technology under Cluster Front Line Demonstration in Samastipur, Bihar, India (Indian Journal of Extension Education, 2022)
Cluster Front Line Demonstration on green gram was conducted during 2016-17 to 2017- 18 in Samastipur district of Bihar to evaluate the performance of improved management techniques in green gram during each year. Performance of demonstrated technology revealed the highest number of nodules/plant at 20 DAS (12.78 & 11.92) & 40 DAS (26.83 & 25.14) and dry weight of nodules/plant at 20 DAS (29.14 & 78.57) & at 40 DAS (26.87 & 73.26) was observed in CFLD. Highest grain yield of (14.20 & 11.20 q/ha) were recorded in demonstrated plot over farmers’ practice during both the years. Lowest technology index was observed in demonstrated technology, 29.0 per cent and 43.8 per cent, respectively. The extension gap varied from 3.62 to 4.855 q/ha. Maximum net returns (Rs. 44,630/ha during 2016-17 and Rs. 40,740/ha in 2017-18) was obtained with higher benefit-cost ratio 2.69 and 2.53, respectively compared to 1.99 in case of local check. The results clearly indicate that use of improved package of practice with scientific intervention under cluster frontline demonstration programme led to increase the productivity and profitability of green gram.